Analyzing the Continuance Intention to Use AI News Anchors for Daily Information Needs: An Expectation Confirmation Theory Approach - Alyah Rahayu; Andika Isma; Fitra Ramadani (Academic Bright Collaboration, 2025)
Artificial intelligence (AI) has begun reshaping news broadcasting through AI-based news anchors that can deliver information efficiently and consistently, yet public acceptance, emotional connection, and accountability for potential errors remain open concerns. This study aimed to analyze users’ continuance intention to use AI news anchors for daily information needs through an Expectation Confirmation Theory, focusing on trust/acceptance, news-delivery quality, and perceived innovation. A quantitative cross-sectional survey was conducted among students aged 18–24 as digitally active users; data were collected via an online Likert-scale questionnaire (15 items across three aspects) and analyzed descriptively to summarize response patterns. The results indicate generally moderate-to-positive evaluations across all aspects: trust and acceptance showed an overall mean of 2.65, news-delivery quality 2.62, and innovation/technology 2.45. At the item level, respondents reported moderate comfort with AI-delivered news (M = 2.51) and moderate belief in accuracy/reliability (M = 2.54); delivery clarity was rated similarly (M = 2.54), while visual appeal showed a relatively stronger influence on viewing interest (M = 2.73). Respondents also expressed interest in AI-related technological advances (M = 2.52) and generally viewed AI news delivery as a positive media direction, while still noting that improvements are needed before AI can fully replace human presenters. These findings imply that media organizations and developers should prioritize more natural and emotionally engaging delivery, strengthen audio-visual realism, and address ethical/regulatory safeguards, concluding that AI news anchors are broadly acceptable to younger audiences but should be positioned as a complement to human presenters rather than a complete substitute.